Comparison of the Effect of 30° and 90° Sloping Position on Pressure Ulcer Incident on Stroke Patients - Arie Sulistiyawati; Yanti Cahyati (GLOBAL HEALTH SCIENCE GROUP, 2020)
Pressure ulcer is a serious problem on stroke patients. The incidence of pressure ulcer has a negative impact on the physical, psychological, social, spiritual and economic burden of the family. One of the efforts to prevent the pressure ulcer is by providing a sleeping position with a 30 ° or 90 ° sloping position. Some hospitals still apply standard operational procedures with a 90 ° sloping position. Therefore, it is important to retest the prevention of pressure ulcer on stroke patients by using both sloping positions. This study aimed to compare the effect of 30 ° and 90 ° sloping position on the incidence of presssure ulcer on stroke patients at Hasan Sadikin Hospital Bandung. This quasi-experimental study involved 34 patients taken using purposive sampling technique which was then divided into groups of 30° and 90° sloping positions (17 respondents each) with the matching was based on the Braden scale. Each group was repositioned every 2 hours and the incidence of pressure ulcer was evaluated every day for 72 hours. The results showed the incidence of pressure ulcer in the 30 ° sloping position group (5.88%) and 90° sloping position (41.18%). Statistical results using exact fisher showed a value of p = 0.039 (<0.05) which means that the incidence of pressure ulcer in the 30° sloping group was significantly less than the result of 90° sloping group. Based on the odds ratio of 11.200, it means that stroke patients who were given a 90° sloping position are at risk 11 times higher risk of pressure ulcer than in stroke patients who were given a 30° sloping position. The conclusion in this study is the incidence of fewer pressure ulcer in a 30 ° sloping position. The results and treatment protocol in this study can be used as one of the considerations in efforts to prevent pressure ulcer, especially in stroke patients. Keywords: pressure ulcer, sloping position, stroke